2021
DOI: 10.1523/jneurosci.2242-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Brain White Matter Plasticity in Sighted Subjects during Tactile Braille Learning: A Longitudinal Diffusion Tensor Imaging Study

Abstract: The white matter (WM) architecture of the human brain changes in response to training, though fine-grained temporal characteristics of training-induced white matter plasticity remain unexplored. We investigated white matter microstructural changes using diffusion tensor imaging at five different time points in 26 sighted female adults during 8 months of training on tactile braille reading. Our results show that training-induced white matter plasticity occurs both within and beyond the trained sensory modality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…However, the structure-function relationship is known to be bidirectional, and training has been shown to induce changes in white matter properties (57). For example, increased FA in somatosensory and visual cortices followed tactile braille reading training (78), increased FA in the right IPS followed juggling training (79), and reduced MD in the left arcuate fasciculus followed intensive reading intervention (80). Thus, the findings of the current study, highlighting individual differences in structural and functional connectivity in the IPS-IFG circuit as potential neuromarkers of response inhibition, suggest that the IFG-IFG and IPS-IFG white matter tracts could be used as potential targets to study intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structure-function relationship is known to be bidirectional, and training has been shown to induce changes in white matter properties (57). For example, increased FA in somatosensory and visual cortices followed tactile braille reading training (78), increased FA in the right IPS followed juggling training (79), and reduced MD in the left arcuate fasciculus followed intensive reading intervention (80). Thus, the findings of the current study, highlighting individual differences in structural and functional connectivity in the IPS-IFG circuit as potential neuromarkers of response inhibition, suggest that the IFG-IFG and IPS-IFG white matter tracts could be used as potential targets to study intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults showed similar changes, along with increased hippocampal gray matter (Boyke et al, 2008 ). A recent study showed increases in white-matter fractional anisotropy in the somatosensory and visual cortex that covaried with behavioral improvement among novices during 8 months of training on tactile braille reading (Molendowska et al, 2021 ). London taxi drivers, whose jobs require them to memorize numerous complicated routes and locations, were found to have hippocampi whose size was directly proportional to their number of years of experience and, hence their age (Maguire et al, 2000 ).…”
Section: How Interventions Can Potentially Accelerate or Decelerate B...mentioning
confidence: 99%
“…From a treatment perspective, the induction of changes in cognition and behaviour can alter brain WM. 22 , 23 Neuroimaging studies have reported changes in WM microstructure following specific training paradigms in motor, 24 , 25 tactile 26 and memory domains. 27 , 28 These findings suggest that WM microstructure, quantified using DTI, dynamically responds to specific training and learning protocols, across different timescales.…”
Section: Introductionmentioning
confidence: 99%